Unconventional Solution for a Complex Elbow Problem, 12 Year Followup: A Case Report - U, Dr. Bharghava Ram; U, Dr. Venkata Ramana; Nishanth, Dr. Ch. S. (International Journal of Innovative Research in Medical Science, 2020)
Introduction: In the past, the indications for elbow arthroplasty were quite limited and included cases of rheumatoid arthritis and post-traumatic arthrosis. Nowadays, the use of elbow arthroplasty may be necessary in selected cases of complex fractures of the elbow, with good functional results. Several methods have been developed to deal with massive bone defects during revision surgery. Complex surgical steps also bring more injury, thus increasing soft tissue‐related complications. The aim of this case report is to evaluate the role of elbow arthroplasty as a primary option and the challenges in subsequent revision surgeries. Case Report: We describe the case of a 14 year old male student, who presented to our emergency department with a side swipe injury to the right elbow on 28 may 2008. He presented with a large open wound with triceps muscle loss and missing entire distal humerus along with a part of olecranon, neurovascular structures intact. After 1 month complete healing of the flap a custom made uncemented total elbow arthroplasty was done through anterior approach. In 12 years he underwent 2 revisions with ROM of 0-80 degrees and 4cm shortening of upper limb. Restricted pronation and supination compensated by shoulder. He completed his graduation and now working as a software engineer. Conclusion: Total elbow arthroplasty is a good alternative for elbow complex fractures. Revision scenarios pose various challenges and sometimes need outside the box thinking. Inserting an ulnar prosthesis into the radius is a novel procedure for patients non reconstructable ulna. It is a safe, quick, and effective treatment with a promising outcome.